1991
DOI: 10.1128/jb.173.22.7330-7339.1991
|View full text |Cite
|
Sign up to set email alerts
|

Roles of porphyrins and host iron transport proteins in regulation of growth of Porphyromonas gingivalis W50

Abstract: Porphyromonas gingivalis (Bacteroides gingivalis) requires iron in the form of hemin for growth and virulence in vitro, but the contributions of the porphyrin ring structure, porphyrin-associated iron, host hemin-sequestering molecules, and host iron-withholding proteins to its survival are unknown. Therefore, the effects of various porphyrins, host iron transport proteins, and inorganic iron sources on the growth of P. gingivalis W50 were examined to delineate the various types of iron molecules used for cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
146
2
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 54 publications
10
146
2
2
Order By: Relevance
“…Our studies were done in Mycoplasma broth containing low levels of iron and thus the 10 mM DP that we used was sufficient to chelate the free iron present in the medium, as demonstrated by previous work (Bramanti & Holt, 1991;Dashper et al, 2004). In addition, previous studies demonstrated haemin-dependent regulation.…”
Section: Discussionmentioning
confidence: 97%
“…Our studies were done in Mycoplasma broth containing low levels of iron and thus the 10 mM DP that we used was sufficient to chelate the free iron present in the medium, as demonstrated by previous work (Bramanti & Holt, 1991;Dashper et al, 2004). In addition, previous studies demonstrated haemin-dependent regulation.…”
Section: Discussionmentioning
confidence: 97%
“…P. gingivalis cannot synthesize the protoporhyrin IX ring and does not have siderophores for alternative bioavailability of hemin [3639]. Therefore, P. gingivalis depends on the host for a supply of heme [40].…”
Section: The Lipid a Structure Is Modulated By Hemin And Temperaturementioning
confidence: 99%
“…Genes hemA, hemL, hemB and hemC encoding the enzymes that are involved in haem biosynthesis pathway cannot be identified in the genome of P. gingivalis [27]. While P. gingivalis can utilize haem from other sources such as serum albumin, transferrin, lactoferrin, haemopexin, catalase, lactoperoxidase and cytochrome [77][78], haemoglobin is the preferred haem and iron source [79].…”
Section: Gingipains In Haem Acquisitionmentioning
confidence: 99%